Assessment of Natural Radioactivity Level in Rice Available in Erbil City, Iraq, and Its Radiological Indices - Muhammad Briem Muhammad; Hiwa H. Azeez (Zanco Journal of Pure and Applied Sciences, 2026)
Natural radioactivity is present in all food types, including rice, and gradually enters the body through the digestive tract. An important metric for estimating population exposure from natural radionuclide intake during regular food consumption is the amount of natural radioactivity present in food. This study used a gamma-ray spectrometer to evaluate the radioactivity levels of naturally occurring radioactive elements in rice samples available in Erbil markets. The 226Ra, 232Th, and 40K activity concentration values in rice samples were within the range (0.212 ± 0.023 to 0.671 ± 0.160) Bq kg-1, (0.104 ± 0.018 to 0.289 ± 0.025) Bq kg-1, and (48.677 ± 3.534 to 153.876 ± 3.885) Bq kg-1, respectively. The activity concentration of the primordial radionuclides was used to determine the annual effective radiation doses from eating rice samples. The total annual effective dosage (IAED) resulting from taking radioactive nuclear in rice varied from (16.600 ± 2.511 to 44.873 ± 2.688) µSv y-1, with the average value of (27.407 ± 7.862) µSv y-1, and was below the UNSCEAR reference limit of 290 µSv y-1. Additionally, the parameters for radiological hazards in rice grains were computed and compared to the international dose safety limit for rice crops.